Factors Influencing the Difference between Indonesian Case-Based Group Reimbursement and Medical Cost for Patients with Chronic Renal Disease Cases in Kasih Ibu Hospital, Surakarta - Mardhatillah -; Didik Tamtomo; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2017)
Backgorund: JKN program has stipulated the INA CBGs reimbursement for the payment of treatment in referral health facilities, including for chronic renal disease which is a disease burden. This study aimed to analyze factors influencing the difference between Indonesian case-based group reimbursement and medical cost for patients with chronic renal disease cases in Kasih Ibu Hospital, Surakarta.Subjects and Method: The study design was an analytic observational with cross sectional design. The study was conducted in Kasih Ibu Hospital Surakarta in August-October, 2017. With a total of 231 subjects sample which was selected by using proportional random sampling. The dependent variable was the difference between Indonesian case-based group reimbursement and medical cost. The independent variables were length of stay, type of class, medical treatment/ surgery, ICU treatment, and medication use. The data were analyzed using multiple linear regression.Result: INA CBGs reimbursement (mean= Rp 6,120,000; SD= Rp 2,330,000) paid by BPJS Kesehatan was lower than actual hospital’s medical care cost (mean= Rp 7,070,000; SD= Rp 4,650,000). Factors profitable for hospitals were medical treatments/ surgery (b= 0.032; p= 0.552). Factors that inflicted financial loss were class 1 care (b= -0.104; p= 0.094), class 2 care (b= -0.033; p= 0.590) compared to class 3 care, length of stay (b= -0.541; p<0.001), medication use in accordance with national formulation (b= -0.183; p= 0.008) and the use of ICU (b= -0.045; p= 0.543). Patients who upgraded the class type (mean= Rp 5,526,074; SD= Rp 1,449,621) was higher than hospital’s medical cost for class 2 (mean= Rp 3,933,767; SD= Rp 1,887,900).Conclusion: Mean of INA CBGs reimbursement on inpatient care of chronic renal disease is lower than the mean of hospital’s medical care cost. Length of stay and doctors’ compliance in using national medication formulation are important determinants to increase medical care cost. Hospital obtains profit from patients who upgrade type of class.Key words: care cost, INA CBGs reimbursement, chronic renal diseaseCorrespondence: Mardhatillah. Kasih Ibu Hospital, Surakarta, Central Java. Email: mardhatillah.bws@gmail.com. Mobile: 089510610891.Journal of Health Policy and Management (2017), 2(2): 117-127https://doi.org/10.26911/thejhpm.2017.02.02.03